IMPLEMENTASI MANAJEMEN PENDIDIKAN KARAKTER DALAM PEMBENTUKAN KARAKTER PESERTA DIDIK DI ERA REVOLUSI INDUSTRI 4.0 - Sambah, Ais Hanifa; Ramadhani, Alfi (Universitas Nahdlatul Ulama Al Ghazali Cilacap, 2022)
Education is a very important thing in human life. With education, humans can achieve what they have aspired to. However, this will not be useful without being balanced with good morals or character in the individual. To get good character or morals in each individual, character education is needed. Character education is needed to balance one's social life. This is necessary so that someone is not eroded by the times, especially in the era of the industrial revolution 4.0. With the existence of character education, it is hoped that it can form the next generation of the nation who is great, capable, and has good character. This research is a qualitative research using data collection techniques by interviewing informants.